Chromosomal Abnormalities in Miscarriages and Maternal Age: New Insights from the Study of 7118 Cases - Anna A. Pendina; Mikhail I. Krapivin; Olga G. Chiryaeva; Lubov’ I. Petrova; Elizaveta P. Pashkova; Arina V. Golubeva; Andrei V. Tikhonov; Alla S. Koltsova; Ekaterina D. Trusova; Dmitrii A. Staroverov; Andrey S. Glotov; Olesya N. Bespalova; et al. (Cells)
Chromosomal abnormalities of the embryo are the most common cause of first-trimester pregnancy loss. In this single-center study, we assessed the frequency and the spectrum of chromosomal abnormalities in miscarriages for each year of maternal age from 23 to 44. Cytogenetic data were obtained by conventional karyotyping of 7118 miscarriages in women with naturally conceived pregnancies. Chromosomal abnormalities were identified in 67.25% of miscarriages. The total incidence of chromosomal abnormalities increased with maternal aging; however, its average change for a one-year increase in maternal age differed between age spans, equaling 0.704% in the span from 23 to 37 years and 2.095% in the span from 38 to 44 years. At the age of 38 years, the incidence rate surged sharply by 14.79% up to 79.01% and then increased progressively up to 94% in 44-year-old women. The spectrum of chromosomal abnormalities in miscarriages was the same for each year of maternal age from 23 to 44 years. However, the proportions of particular chromosomal abnormalities differed between karyotypically abnormal miscarriages in younger and older women. The proportions of trisomy 16, polyploidy, monosomy X, mosaic aneuploidies, and structural rearrangements decreased with increasing maternal age. In contrast, the proportions of multiple aneuploidies and regular trisomies 13, 15, 18, 21, and 22 showed an upward trend with maternal aging. To summarize, despite the increase in the total incidence of chromosomal abnormalities in miscarriages with maternal aging, the rate of change differs for younger and older women, being three times lower in the former than in the latter. Moreover, the proportion of some abnormalities in karyotypically abnormal miscarriages shows a steady growth, whereas the proportion of others becomes increasingly low with maternal aging, most probably due to the age-dependent prevalence of different molecular and cellular defects.